Preventing shivering with adjuvant low dose intrathecal meperidine: A meta-analysis of randomized controlled trials with trial sequential analysis. Issue 1 (December 2017) - Lin, Yu-Cih; Chen, Chien-Yu; Liao, Yuan-Mei; Liao, Alan; Lin, Pi-Chu; Chang, Chuen-Chau
Abstract The aim of this systematic review and meta-analysis is to evaluate the pros and cons of adjuvant low dose intrathecal meperidine for spinal anaesthesia. We searched electronic databases for randomized controlled trials using trial sequential analysis (TSA) to evaluate the incidence of reduced rescue analgesics, shivering, pruritus, nausea and vomiting when applying adjuvant intrathecal meperidine. Twenty-eight trials with 2216 patients were included. Adjuvant intrathecal meperidine, 0.05–0.5 mg kg−1, significantly reduced incidence of shivering (relative risk, RR, 0.31, 95% confidence interval, CI, 0.24 to 0.40; TSA-adjusted RR, 0.32, 95% CI, 0.25 to 0.41). Intrathecal meperidine also effectively reduced need for intraoperative rescue analgesics (RR, 0.27, 95% CI, 0.12 to 0.64; TSA-adjusted RR, 0.27, 95% CI, 0.08 to 0.91) and the incidence of pruritus was unaffected (RR, 2.31, 95% CI, 0.94 to 5.70; TSA-adjusted RR, 1.42, 95% CI, 0.87 to 2.34). However, nausea and vomiting increased (RR, 1.84, 95% CI, 1.29 to 2.64; TSA-adjusted RR, 1.72, 95% CI, 1.33 to 2.23; RR, 2.23, 95% CI, 1.23 to 4.02; TSA-adjusted RR, 1.96, 95% CI, 1.20 to 3.21). Under TSA, these results provided a sufficient level of evidence. In conclusion, adjuvant low dose intrathecal meperidine effectively attenuates spinal anaesthesia-associated shivering and reduces rescue analgesics with residual concerns for the nausea and vomiting.